2007
DOI: 10.1086/520088
|View full text |Cite
|
Sign up to set email alerts
|

Potential Associations between Hematogenous Complications and Bacterial Genotype inStaphylococcus aureusInfection

Abstract: Background. The impact of bacterial clonality on infections caused byStaphylococcus aureus is unclear. Methods. Three hundred seventy-nine S. aureus isolates (125 methicillin-resistant S. aureus [MRSA] and 254 methicillin-susceptible S. aureus [MSSA]) were genotyped by spa typing and multilocus sequence typing. For MRSA isolates, the staphylococcal chromosomal cassette mec (SCCmec) element was also typed. Three clinical categories were identified: nasal carriage only ( ), uncomplicated infection ( ), and bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
147
7
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(173 citation statements)
references
References 33 publications
18
147
7
1
Order By: Relevance
“…4). For example, Fowler et al reported that EMRSA-16 and related isolates (ST36) were significantly associated with increased severity of infection (15). These findings seem at variance with our mouse infection data, but it is important to note that the infections caused by these CC30 strains occurred in the healthcare setting, and as such, infected individuals had underlying risk factors for infection (13,15).…”
Section: Hla Segregates Phage-type 80/81 and Southwest Pacific Clonescontrasting
confidence: 69%
See 2 more Smart Citations
“…4). For example, Fowler et al reported that EMRSA-16 and related isolates (ST36) were significantly associated with increased severity of infection (15). These findings seem at variance with our mouse infection data, but it is important to note that the infections caused by these CC30 strains occurred in the healthcare setting, and as such, infected individuals had underlying risk factors for infection (13,15).…”
Section: Hla Segregates Phage-type 80/81 and Southwest Pacific Clonescontrasting
confidence: 69%
“…For example, Fowler et al reported that EMRSA-16 and related isolates (ST36) were significantly associated with increased severity of infection (15). These findings seem at variance with our mouse infection data, but it is important to note that the infections caused by these CC30 strains occurred in the healthcare setting, and as such, infected individuals had underlying risk factors for infection (13,15). Further, S. aureus strains with defective Agr gene regulatory systems (such as the contemporary CC30 hospital isolates studied here) typically have increased levels of surface protein expression, such as protein A and EMRSA-16, and related CC30 MSSA clones are known to be prominent human nasal colonizers (13,15).…”
Section: Hla Segregates Phage-type 80/81 and Southwest Pacific Clonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in prevalence of skeletal infections of poultry to become a major cause of lameness in the industry correlates with the emergence and wide dissemination of the ST5 poultry subtype. Of note, a previous study reported that the ST5 clonal complex is associated with increased frequency of hematogenous infections of humans, including osteomyelitis (26), consistent with the largely skeletal tropism of infections caused by the poultry ST5 clade. The reduction in the biodiversity of chickens in the broiler poultry industry such that a very small number of breeding lines are supplied for global consumption promotes the spread of opportunistic pathogens that are resident on those birds and could select for infectious diseases to which those animals are genetically predisposed.…”
Section: The Poultry St5 Strain Ed98 Exhibits Enhanced Resistance Tomentioning
confidence: 61%
“…In contrast, Fridkin and colleagues found that 77% of CA-MRSA infections were of skin and soft tissue (mainly abscesses and cellulitis), with only 6% causing invasive disease (16). In the United States, USA100, USA200, and USA500 constitute the most abundant isolates from health care-associated infections, whereas USA300 and USA400 account for the greatest number of CA-MRSA isolates (11,17,23,47,86). These differences in invasive disease and mortality for health care-associated MRSA versus CA-MRSA infections could suggest that health care-associated strains are more virulent than those causing community infections.…”
Section: Ca-mrsa Virulence and Pathogenesismentioning
confidence: 98%